Performance analysis software for reinforced concrete beam-columns under various load and displacement patterns - Rohleder, Schyler (Kansas State University, 2017)
Performance-based building design is a necessity in geographic locations where buildings are susceptible to large earthquakes and high winds. This design method requires an analysis of the performance of the structural system with loadings and deflections caused by earthquakes and wind. Current design codes include the load intensity in analysis procedures, but do not consider the effect of load pattern in the performance analysis of reinforced concrete columns. Because a thorough analysis must take into consideration load pattern and load intensity, computer software is ideal to analyze these systems. A computer program was originally developed by Esmaeily (USC_RC), and was revised later to be renamed (KSU_RC) in order to make the analysis of concrete column performance accurate, yet simple for design purposes. This analytical tool used analytical methods and material models, verified against experimental data, to accurately predict the performance of reinforced concrete columns under various loading conditions, including any pattern in lateral direction and independently variable axial load. However, the program was limited to circular, rectangular, hollow circular and rectangular sections and uniaxial lateral curvature and displacement. The next generation of the program, KSU RC 2.0, was developed to overcome the aforesaid limitations.
Keywords: Concrete Analysis Software; Concrete Beam-Columns; Various Load and Displacement Patterns